2015
DOI: 10.5539/jfr.v4n3p46
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Preferences for Environmental Sustainability in Fruit Production by United Kingdom and Japanese Consumers

Abstract: Reduction of carbon intensity of high volume grocery products is potentially a major contributor in meeting climate targets. In a choice experiment concerning fruit purchase decisions in the United Kingdom and Japan, this study estimates consumer willingness to pay for sustainability attributes of production alongside vitamin content, including water use efficiency, waste and packaging, and carbon emissions. Results indicate that sustainability attributes significantly influence consumers' fruit purchase decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(48 reference statements)
1
12
1
Order By: Relevance
“…The food safety and environmental attributes have been found to be valued relatively high in Japan, in particular in the context of BSE‐tested domestic beef (Aizaki, Sawada, Sato, & Kikkawa, ) and choice of eco‐labelled domestic salmon (Uchida et al, ). In fruit products, both Japanese and UK consumers have been found to value environmental aspects (e.g., carbon reduction and water efficiency) more than increments in nutritional (vitamins) attributes (Tait et al, ), which was not found in the present study. This could be due to the attribute description being health‐enhancing rather than nutritional (source of vitamins) related.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…The food safety and environmental attributes have been found to be valued relatively high in Japan, in particular in the context of BSE‐tested domestic beef (Aizaki, Sawada, Sato, & Kikkawa, ) and choice of eco‐labelled domestic salmon (Uchida et al, ). In fruit products, both Japanese and UK consumers have been found to value environmental aspects (e.g., carbon reduction and water efficiency) more than increments in nutritional (vitamins) attributes (Tait et al, ), which was not found in the present study. This could be due to the attribute description being health‐enhancing rather than nutritional (source of vitamins) related.…”
Section: Resultscontrasting
confidence: 65%
“…Consistent with this view, UK consumers favour the idea of combining FT and organic labels (Sirieix et al, 2013). There is also an increasing amount of literature examining environmental eco‐labels or certification (Tait et al, ; Ubilava et al, ; Van Loo, Caputo, Nayga, Seo, & Verbeke, ) and improved environmental standards in food production (Moser, Schaefers, & Meise, ; Viegas et al, ; Yue et al, ; Tait, Saunders, & Guenther, ). Many of these studies found a positive WTP for environmental attributes, particularly for domestic products (Ortega et al, ; Uchida, Onozaka, Morita, & Managi, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental concerns and social trust embedded in consumers, however, may have driven consumer purchase intentions towards abnormally-shaped FVs. Another interesting variable reported was the environmental sustainability of the FVs [30]. We found that consumers preferred fruit that involved greater reductions in carbon emissions, more efficient use of water resources, and less waste/packaging.…”
Section: Consumer Perceptions Of Fvsmentioning
confidence: 83%
“…When consumers were asked to define 'good quality', most agreed that nutrition was a strong criterion [27]. Consumers also preferred higher levels of vitamins when they purchased fruit [30]. Other variables associated with their purchases of FVs included cleanliness, colour, taste, packaging, smell, and involvement in religious processes [27].…”
Section: Consumer Perceptions Of Fvsmentioning
confidence: 99%
“…The authors also found that consumer WTP increased as the amount of pesticides used decreased. Tait et al (2015) found that consumers in the United Kingdom and Japan were willing to pay extra for fruits with sustainable attributes including carbon emissions reduction, water efficiency, and waste/packaging reduction. In China, consumers were willing to pay extra for both the green label (''limited use of synthetic chemicals during production'') and the organic label on rice (Liu et al, 2017).…”
mentioning
confidence: 99%